Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim (Journal of Agricultural and Food Chemistry, 2004)
Nutritionists are interested in functional assays of tannins that do not require time-consuming and expensive extraction, such as the 14C-labeled poly(ethylene glycol) (PEG)-binding (PEG-b) assay. This paper reports the application of near-infrared (NIR) spectroscopy to determine the percentage of PEG binding, in place of the 14C-labeled PEG-b assay of tannin, in Mediterranean woodland vegetation. Calibration was done with 53 samples from 14 species and was validated on 25 samples from 10 species. PEG-b ranged between 1.4 and 20.7% in the samples. The calibration obtained by using the modified partial least-squares (MPLS) method, with all wavelengths in the 1100?2500 nm range combined, and the validation were reasonably linear (R?2 = 0.96 and 0.91, respectively). The accuracies, estimated from the standard errors of cross-validation and prediction, were ±1.6 and ±1.7% PEG-b, respectively. The NIRS-aided procedure proposed here can serve as an accurate, inexpensive, time-saving, and environment-friendly functional assay of tannin in Mediterranean browse. Keywords: NIRS; goats; nutrition; poly(ethylene glycol); pasture
From Duplicate 1 (Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim)
Keywords: Animal Nutritional Physiological Phenomena; Animals; Carbon Radioisotopes; Fabaceae; Fabaceae: chemistry; Goats; Hydrolyzable Tannins; Hydrolyzable Tannins: analysis; Near-Infrared; NIRS; nutrition; pasture; poly(ethylene glycol); Polyethylene Glycols; Polyethylene Glycols: metabolism; Spectroscopy

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy